(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
In this Ravi River basin in Himachal Pradesh there are total 1287 villages and out of this 68 percent villages are inhabited and about 32 percent villages are uninhabited. The overall population density of Ravi River basin in H.P is increased to 78 in 2011 in comparison to previous census density of 69. The decadal growth rate of this basin is 11.56% in 2011 census but Chaurah and Saluni tehsils has higher growth in comparison to Holi (-2.89%) and Multhan (-7.81%) tehsil’s, the growth rate of population has in negative position due to migration of population from Holi and Multhan to Baijnath and Palampur areas of Kangra District. The overall literacy rate of Ravi River basin are increased to 61.90% in 2011 in comparison to previous census but on sex wise basis it is 70.16% in males and only 53.67% in females. The total population in 2011 Census of Ravi River basin in Himachal Pradesh increased to 422682 from previous census population of 373833 but in Holi tehsil and Bara Bhangal Village of Multhan tehsil, the population was decreased due to migration of people to various places of Kangra district. The overall sex ratio of Ravi River basin in H.P. is 955 Women against 1000 males in 2001 census but it is increased to 982 in 2011 census. The overall 0-6 age group sex ratio in Ravi River basin in H.P is 938 in 2001 census and it increased to 967 in 2011 census. In this basin 23.41% people belongs to scheduled caste category, but on tehsil wise it is 29.13% in Chaurah as high and 9.79% as low in Bharmour tehsil of this basin. It is found out that in Bara Bhangal Village of Multhan tehsil has no scheduled caste population. In Ravi River basin 21.94% people belongs to scheduled tribe population, but on tehsil wise basis it is 84.66% in Bharmour and it is high in this basin and there is no tribal population found in Bara Bhangal village of Multhan tehsil of this Ravi River basin in Himachal Pradesh.